Determination of cercosporin (CER) phytotoxin isolated from infected peanut leaves by using adsorptive stripping square wave voltammetry - Marchiando, Nancy Cristina (2005)
The adsorptive accumulation of cercosporin (CER) phytotoxin on glassy carbon (GC) electrodes from 1 M HClO4 aqueous solutions is used to detect and quantify the phytotoxin isolated from infected leaf tissue collected from field-grown peanut in five locations in southern regions of the Provinces of Cordoba and San Luis, Argentina. The adsorptive stripping square wave voltammetry (ASSWV) is employed to ´ perform the quantitative determination of CER in naturally infected extracts. Thin layer chromatography (TLC) and HPLC were used to verify the presence of CER in extracts. Values of Rf = 0.23 and Rf = 0.15 were determined for CER by TLC when extracts were dissolved in ethyl acetate (EA) and acetone (Ac), respectively, while a retention time of 6.13 min (Ac) was determined by HPLC. The recovery percentage of CER using ASSWV was determined by employing healthy peanut leaf tissue spiked with standard CER. The application of standard addition method was used to determine the recovery percentage as well as the CER contamination level in infected extracts. A recovery percentage of 93.27% was obtained with a relative standard deviation of 21.8% for a solution concentration of 1.04 × 10−6 mol dm−3 (n = 11). The limit of detection for a signal to noise ratio of 3:1 was about 6 ppb and the quantitation limit was about 50 ppb. The pondered relative standard deviation of 9.5% was calculated for the ASSWV method. Results found for CER contamination level in extracts through the electroanalytical method here proposed are in reasonable agreement with those values determined by using HPLC measurements.